Exploring evidence use and capacity for health services management and planning in Swiss health administrations: A mixed-method interview study. - Aron Baumann; Kaspar Wyss (PLoS ONE)
Background Health administrations require evidence, meaning robust information, data, and research, on health services and systems. Little is known about the resources and processes available within administrations to support evidence-informed policymaking. This study assessed Swiss health administrations' capacity for evidence use and investigated civil servants' needs and perspectives regarding the role and use of evidence in health services management and planning. Methods In this mixed-method study, we interviewed civil servants from Swiss German-speaking cantonal health administrations. We quantitatively assessed administrations' organization-level capacity by applying six structured interviews using an existing measurement tool (ORACLe). Individual-level needs and perspectives regarding evidence use and capacity were qualitatively explored with twelve in-depth interviews that were analyzed using the framework method. Findings Respondents indicated moderate evidence-use capacity in all administrations. Administrations displayed a similar pattern of high and low capacity in specific capacity areas, generally with considerable variation within administrations. Most administrations indicated high capacity for producing or commissioning evidence and close relationships with research. They showed limited capacity in the documentation of processes and availability of tools, programs, or training opportunities. Administrations place the responsibility for engagement with evidence at the level of individual civil servants rather than at the organizational level. Although administrations highly value evidence-informed policymaking and consider it vital to effective health services management and planning, they face significant constraints in accessing evidence-specific resources and receive little organizational support. Administrations rely on external capacity to compensate for these limitations and engage with evidence pragmatically. Conclusion Our findings indicate moderate and improvable capacity for evidence use in Swiss health administrations that place limited value on organizational support. Besides strengthening organizational support, leadership buy-in, particular staff needs, and balancing the implementation of specific measures with the provision of more general resources should be considered to unlock the potential of strengthened engagement with evidence.